ESTRATEGIAS DE APRENDIZAJE Y SU IMPLICACIÓN EN EL RENDIMIENTO ACADÉMICO DE ESTUDIANTES CON NECESIDADES EDUCATIVAS ESPECIALES. - ACOSTA ZAMBRANO DANIELA ELIZABETH (2024)
This case study addresses the diversity of special educational needs (SEN) in the Armando Pareja Coronel Educational Unit, with the objective of identifying the relationship between learning strategies and the academic performance of students with special educational needs in the Educational Unit. A qualitative approach and a descriptive methodology were used, as a source of research, documentary consultation, and finally, observation and interviews were used as a data collection technique. The results show a significant variety of SEN, from physical and sensory disabilities to learning difficulties. An adaptation of learning strategies is observed, but with inconsistencies in access to adapted resources. The interview with the director highlights the positive perception of adapted strategies in the academic performance of students with SEN, although challenges in their implementation are identified. It is concluded that it is crucial to develop a more systematic approach in the implementation of these strategies, improve accessibility to resources and encourage collaboration between teachers and special education specialists. In summary, the importance of inclusive and equitable education is highlighted to ensure the success of all students, regardless of their individual needs.